UV-VUV synchrotron radiation spectroscopy of NiWO4 - Kuzmin, A.; Pankratov, V.; Kalinko, A.; Kotlov, A.; Shirmane, L.; Popov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Photoluminescence and excitation spectra of microcrystalline and nanocrystalline nickel tungstate (NiWO4) were measured using UV-VUV synchrotron radiation source. The origin of the bands is interpreted using comparative analysis with isostructural ZnWO4 tungstate and based on the results of recent first-principles band structure calculations. The influence of the local atomic structure relaxation and of Ni2+ intra-ion d–d transitionson the photoluminescence band intensity are discussed.